1992
DOI: 10.1212/wnl.42.12.2300
|View full text |Cite
|
Sign up to set email alerts
|

Strong correlation between the number of CAG repeats in androgen receptor genes and the clinical onset of features of spinal and bulbar muscular atrophy

Abstract: X-linked spinal and bulbar muscular atrophy (SBMA), a motor neuron disease associated with androgen insensitivity, is caused by androgen receptor gene mutations with an increased number of tandem CAG repeats in exon 1. We investigated the increased number of CAG repeats in androgen receptor genes of 19 SBMA patients and found that this correlated strongly with the age at onset of muscle weakness. Thus, SBMA is the first genetic disease in which a strong correlation between the degree of genetic abnormality (nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(82 citation statements)
references
References 0 publications
5
74
0
2
Order By: Relevance
“…In two studies 10,11 correlation between the repeat length and more severe symptoms and earlier onset of SBMA is reported, but in two other studies 20,21 no correlation was found. In our study, weak negative correlation was found between the CAG repeat length and the age of onset in the 95 SBMA patients with defined ages at onset, but when the patients from different countries were examined separately, the correlation was detected only in the Japanese patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In two studies 10,11 correlation between the repeat length and more severe symptoms and earlier onset of SBMA is reported, but in two other studies 20,21 no correlation was found. In our study, weak negative correlation was found between the CAG repeat length and the age of onset in the 95 SBMA patients with defined ages at onset, but when the patients from different countries were examined separately, the correlation was detected only in the Japanese patients.…”
Section: Discussionmentioning
confidence: 95%
“…The longer the repeat, the more severe the symptoms are and the earlier the onset of the disease. 10,11 Most Finnish SBMA patients come from the district of Vaasa in Western Finland. 3 We have shown that all the Finnish families share identical alleles for at least five nearby markers around the AR gene.…”
Section: Introductionmentioning
confidence: 99%
“…In SBMA, a polymorphic CAG repeat with 14 -32 CAGs expands to 40 -62 CAGs in the first exon of the androgen receptor (AR) gene (La Spada et al, 1991;Tanaka et al, 1996). CAG repeat size is inversely correlated with the age at onset and positively correlated with disease severity in SBMA (Doyu et al, 1992;Igarashi et al, 1992;La Spada et al, 1992). The histopathologic hallmarks of SBMA are lower motor neuronal loss (Sobue et al, 1989), diffuse nuclear accumulation, and nuclear inclusions (NIs) of expanded polyQ mutant AR in the residual motor neurons in brainstem and spinal cord as well as in some other visceral organs (Li et al, 1998a,b;.…”
Section: Introductionmentioning
confidence: 99%
“…In SBMA patients, a normally polymorphic CAG repeat (10 -36 CAGs) expands to 38 -66 CAGs. The number of CAGs is inversely correlated with the age of onset of the disease (2)(3)(4). To date, seven other CAG repeat diseases have been identified, including Huntington's disease (5), dentatorubralpallidoluysian atrophy (6,7), and five spinocerebellar ataxias: 1, 2, 3, 6, and 7) (8 -14).…”
mentioning
confidence: 99%